From High Discipline Referrals to High-Engagement Classrooms: A Design-Based Approach to Creating a Campus-Wide Culture of Positive Learning Support for At-Risk Student Populations through Transforming Educators’ Instructional Teaming Practices - Claudet, Joseph G. (Advances in Social Sciences Research Journal, 2024)
Instructional leaders in many school districts throughout the United States are increasingly confronted with spiraling numbers of discipline referrals from teachers who are unable to manage the off-task behaviors and discipline infractions of the growing percentages of diverse, academically at-risk students populating their classrooms. Many of these at-risk students, who come from families that are economically disadvantaged and have culturally rich and linguistically diverse backgrounds, have become stigmatized and minoritized by an education system whose curricula are often woefully inadequate in being able to meet the unique social and academic support needs of these diverse learners. This article profiles how one high school principal and his instructional turnaround leadership task force colleagues working in a high diversity urban school district utilized multi-leveled data analysis investigative thinking and innovative professional learning program design strategies derived from the education improvement science literature to implement a comprehensive intervention program for ninth through twelfth grade teams of core content teachers and their instructional supervisors. The specific goals of the intervention program were to: 1) change educators’ entrenched pedagogical thinking and instructional planning mindsets regarding the motivation levels and learning capabilities of the high discipline referral students who regularly engage in off-task disruptive behaviors in their classrooms; and 2) transform teachers’ instructional data teaming practices to better serve the academic learning support needs of the campus’s minoritized students. The design-based approach to instructional improvement employed in the high school case study leveraged the use of multiple cycles of new knowledge and skills acquisition, critical self-reflection, and immersive professional learning to assist educators in exploring how to engage together in authentic data teaming and data analysis–informed differentiated instructional planning to craft high-engagement classroom learning environments and interactive instructional units to effectively address the academic development and support needs of the campus’s diverse, at-risk learners.